(untitled) (International Journal of Physiotherapy, 2024)
Background: Neck pain is a common musculoskeletal problem that significantly causes disability. Exercise therapy is effective in decreasing pain and improving the functional ability among patients with neck pain. In this study, we evaluated the effectiveness of a home-based neck stabilization exercise program in pain and neck disability among female college students with non-specific neck pain (NSNP). Methods: A quasi-experimental study with a single group pre-test post-test was conducted in Jazan, Saudi Arabia. Sixteen participants with NSNP underwent six weeks of training, which included one face-to-face session and 17 sessions of home-based exercise training. The pre-test and post-test values were obtained before and after six training sessions using the Numerical pain rating scale and neck disability index for pain intensity and neck disability, respectively. Results: A significant reduction in neck pain intensity and disability was observed, with a mean difference of 2.88 and 12.4, respectively. The calculated ‘t’ value using the paired ‘t’ test for the numerical pain rating scale was 10.022 (p<0.01), and the neck disability index was 4.934 (p<0.01). Conclusion: Based on the statistical analysis and clinical significance, the present study provides preliminary evidence that a home-based neck stabilization exercise program reduces pain and neck disability among female college students with NSNP.